2018
DOI: 10.1063/1.5019782
|View full text |Cite
|
Sign up to set email alerts
|

Action-at-a-distance metamaterials: Distributed local actuation through far-field global forces

Abstract: Mechanical metamaterials are a sub-category of designer materials where the geometry of the material at the small-scale is rationally designed to give rise to unusual properties and functionalities. Here, we propose the concept of “action-at-a-distance” metamaterials where a specific pattern of local deformation is programmed into the fabric of (cellular) materials. The desired pattern of local actuation could then be achieved simply through the application of one single global and far-field force. We proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…These two lattice structures showed narrow-waisted and barrel-shaped deformations. A similar relationship was noticed by Hedayati et al [57].…”
Section: Compression Tests Under Impact Loading Conditionssupporting
confidence: 88%
“…These two lattice structures showed narrow-waisted and barrel-shaped deformations. A similar relationship was noticed by Hedayati et al [57].…”
Section: Compression Tests Under Impact Loading Conditionssupporting
confidence: 88%
“…Page 10 of 37 AUTHOR SUBMITTED MANUSCRIPT -SMS-107709 .R1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d M a n u s c r i p t 11 where η is non-negative consistency coefficient. The superscript D indicates deviatoric component of gp T that has been assumed to contribute in the plastic evolution.…”
Section: Ii) Mechanism Of Cold Programmingmentioning
confidence: 99%
“…Their experimental and numerical results indicated that the proposed lattices exhibited extreme Poisson's-ratio variations between -0.7 and 0.5 over large tensile deformations up to 50%. Hedayati et al [11] proposed action-at-adistance 3D printed mechanical metamaterials by grading designs of auxetic and conventional unit cells with changing Poisson's ratios. Rafsanjani et al [13] proposed a multi-stable 2-D mechanical metamaterial comprising a periodic arrangement of snapping units with tunable tensile behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging design strategy explores the capacity of the internal architecture 2 of 12 to transfer local deformation through the metamaterial. In this case of so-called action-at-a-distance metamaterials, the internal architecture may define the involved geometrical changes observed on the surface of the metamaterial in response to applied mechanical stimuli [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%